Comparison between solar utilization of a closed microalgae-based bio-loop and that of a stand-alone photovoltaic system. (May 2015) - Jin, Qiang; Chen, Lei; Li, Aimin; Liu, Fuqiang; Long, Chao; Shan, Aidang; Borthwick, Alistair G.L.
Graphical abstract: Highlights: A closed microalgae-based bio-loop is assessed according to the broad LCA. The bio-loop appears more competitive than the stand-alone PV system. Operational energy consumption constitutes the main negative contribution. The overall performance is significantly improved by pressurization and coupling. Abstract: This study compared the solar energy utilization of a closed microalgae-based bio-loop for energy efficient production of biogas with fertilizer recovery against that of a stand-alone photovoltaic (PV) system. The comparison was made from the perspective of broad life cycle assessment, simultaneously taking exergy to be the functional unit. The results indicated that the bio-loop was more environmentally competitive than an equivalent stand-alone PV system, but had higher economic cost due to high energy consumption during the operational phase. To fix the problem, a patented, interior pressurization scheduling method was used to operate the bio-loop, with microalgae and aerobic bacterial placed together in the same reactor. As a result, the overall environmental impact and total investment were respectively reduced by more than 75% and 84%, a vast improvement on the bio-loop.